Sustainable ecotourism in small island destinations: A strategic planning perspective - Dila Puspa; La Baco Sudia; Kahirun; La Gandri; La Ode Muhammad Erif; Lies Indriyani; Eka Rahmatiah Tuwu (Social, Ecology, Economy for Sustainable Development Goals Journal, 2026)
Background: The sustainable development of coastal ecotourism requires context-specific strategies that balance economic opportunities with ecological preservation. Sahara Beach in Longa Village, Wangi-Wangi District, Wakatobi Regency, holds significant potential as an ecotourism destination but remains underdeveloped. This study aims to design a strategic development plan to enhance its competitiveness and sustainability. Methods: A mixed-method approach was applied, combining qualitative and quantitative descriptive analysis. SWOT analysis served as the primary tool to identify internal strengths and weaknesses as well as external opportunities and threats, thereby guiding the formulation of strategic priorities for sustainable ecotourism planning. Finding: The findings reveal that the Strengths–Opportunities (S-O) aggressive strategy offers the most effective pathway for Sahara Beach’s development. Key strategic priorities include: (1) strengthening digital-based promotional campaigns to broaden market reach and increase tourist arrivals, and (2) leveraging government support alongside cross-sectoral partnerships to accelerate the improvement of infrastructure and tourism facilities. These strategies are designed to simultaneously enhance ecological conservation, socio-cultural preservation, and economic benefits for local communities. Conclusion: This study provides actionable insights for policymakers and stakeholders in Wakatobi, highlighting the value of SWOT-based approaches in ecotourism planning. Beyond its local application, the study contributes to the broader discourse on sustainable coastal tourism across small island regions. Ultimately, Sahara Beach has the potential to emerge as a competitive and resilient ecotourism hub while delivering meaningful socio-economic outcomes for surrounding communities. Novelty/Originality of this article: The novelty of this study lies in its application of a SWOT-based mixed-method approach specifically tailored for small-island coastal ecotourism planning in Indonesia.